Cerebrovascular Profile Assessment in Parkinson’s Disease Patients - Perju-Dumbrava, Laura; Muntean, Maria-Lucia; Fior Muresanu, Dafin (CNS & Neurological Disorders - Drug Targets, 2014)
Introduction: Parkinson’s disease (PD) is one of the most common neurodegenerative diseases, and PD patients can present a variety of comorbidities that increase with age. Among them, cardiovascular and cerebrovascular diseases are the most prominent. Aim: To assess the cardiovascular and cerebrovascular profiles of PD patients. Patients and Methods: The cardiovascular risk factors of 126 PD patients were assessed according to laboratory tests (fasting blood sugar, serum cholesterol, triglycerides, and total lipids), Doppler ultrasound examinations and personal histories of cerebrovascular disease (ischemic/hemorrhagic), cardiovascular disease (myocardial infarct or angina confirmed by electrocardiogram), hypertension and diabetes. All patients underwent cerebral structural imaging procedures: computed tomography or magnetic resonance imaging. Results: 58.73% of the patients presented with hypertension, with a slight predominance of female patients (65.38% vs 47.92%, P = 0.05). Carotid or vertebral atheromatosis was present in 39 (30.95%) and 28 (22.22%) of patients, respectively, and was statistically correlated with the presence of ischemic lesions on cerebral imaging. Regarding the computed tomography findings, 33 patients (28.21%) presented with cortical atrophy that was not correlated with any of the investigated cardiovascular factors. Conclusions: Our findings indicate that risk factors for cardiovascular and cerebrovascular diseases are common in PD patients, possibly due to their older age. The presence of atherosclerosis and its complications can be detected in cerebral imaging studies.
Keywords: Parkinson' s disease